Penatalaksanaan Fisioterapi Pada Kondisi Osteoatritis Knee Bilateral Di RS PKU Muhammadiyah Yogyakarta - Sari, Rinda Aulia Novita; , Dwi Rosella Komala Sari, S.Fis.,M. Fis (2015)
Background : osteoarthritis is a joint symptome that cause decreased of cartilage of joint, and then appears bump of bone in surface of joint (osteofit),which is characterized by an increase in pain, limitation of motion and functional limitation. Modalities are given to this condition are Infra Read (IR) and Transcuteneous Electrical Nerve Stimulation (TENS). Objective : To know the benefits of modalities IR, TENS for reducing pain, increasing range of motions, and increasing functional activities in bilateral osteoatritis of the knee. Metode : Physiotherapy methods used in the case are IR and TENS. The evaluation was done by the method of measurement of pain by visual describtive scale, range of motion by goniometer and functional activity by Jette Scale. Results : After 6 treatments of therapy shows a decrease in press pain T1:mild pain to T6: no pain, motion pain T1: pain is no very severe to T6: mild pain; increase active range of motion knee dextra active motion T1: S:0º-0º -110ºtoT6: S:0º -0º-115º, increase range of motion knee dektra pasiveT1:S: 0 º -0 º -115º toT6:S: 0 º -0 º -120º; increase range of motion knee sinistra active motion T1 : S : 0 º - 0 º - 120º to T6 : S:0º-0º -125º, increase range of motion knee sinistra passive motion T1 :S: 0 º -0 º -120º to S: 0 º -0 º -130º ; increase in funcional activity T1 : 31 to T6 : 21. Conclusion : In the case of modalities IR, TENS can decrease pain, improve LGS, and increase functional activity.